Analysis of modern telecommunications: data transmission via GSM channel - Sukhno, Р. Y.; Sotnik, S. V. (Видавництво ОНТУ, 2024)
The article discusses modern technologies of telecommunications with focus on data transmission through GSM channels. Key aspects such as advantages and disadvantages of this communication standard are studied. Particular attention is paid to processes of encoding and compression, which ensure efficiency and reliability of communication. Analysis of automation in data management shows how adapting technologies can improve quality of communication. The results of the study confirm the relevance of GSM in various fields, emphasizing its importance in face of rapidly changing requirements of our time. The identified advantages and disadvantages of technology make it possible to optimize data transmission processes, reducing costs and improving quality of communication. The results can also serve as basis for further research in field of transition to latest standards, which ensures competitiveness in modern telecommunications market.
Keywords: data transmission; GSM channel; wireless communication; network analysis